Calibration of a torque measuring device using an electromagnetic force torque standard machine. (December 2019) - Nishino, Atsuhiro; Fujii, Kenichi
Highlights: The EMTSM is torque standard machine based on the principle of the Kibble balance. The calibration range of the EMTSM was expanded up to 0.27 μN·m. A TMD could be calibrated by using the EMTSM according to the existing procedures. Abstract: To realize a microtorque standard, we have been investigating the principle of torque generation with an electromagnetic force by referring to the Kibble balance method used for the redefinition of the kilogram in the International System of Units (SI). In a previous study, we developed an electromagnetic force torque standard machine (EMTSM) to create precise torque using the Kibble balance method and realize an SI-traceable, non-gravity-based torque standard. To assure the SI traceability of torque standards used in Japanese industry, it is necessary to apply the calibration procedure for torque measuring devices (TMDs) described in the Japan Measuring Instruments Federation guideline JMIF-015 when calibrating TMDs with torque standard machines (TSMs). In this study, we developed a calibration procedure for TMDs using the EMTSM with calibration procedures based on JMIF-015. In addition, we introduced a highly accurate programmable voltage/current source to expand the calibration range of the EMTSM to 0.27 μN∙m to 100 mN∙m. The relative expanded uncertainty W tsm_e of the torque realized by the EMTSM was evaluated to be 1.7 × 10 −3, with a coverage factor k of 2 over this torque range. The calibration results for a low-capacity TMD using the EMTSM with calibration procedures based on JMIF-015 were equivalent to those of a typical strain gauge torque transducer calibrated using a deadweight torque standard machine.